Standardization The Effect of Parent’s Social Demographic Conditions on Working Hours among Child Labors in Makassar City - Nursita, Lisa; Putri, Andi Tenri Lawa (Jurnal Ilmiah Ilmu Administrasi Publik, 2018)
A long working hour will negate child’s Physical and Psychological states. For this reason, it is paramount to investigate the surrounding factors which may affect the working hours among child labors. The finding potentially bring information to stakeholders and authorities which later may assist them in taking the best decision to deal with child labors and further reduce the working hours. This study aimed to investigate the effect of the household education, income, parents’ age, and number of dependents on the child’s working hour in Makassar City. The data were collected from 100 respondents using survey and the data were analyzed with multiple regression analysis technique. The results found that the parent’s education and income negatively and significantly predicted working hours among child labors. Thus, this study suggested that the authorities should reduce the poverty so the families do not further employ their children to support their financial needs. The authorities should also empower the community to shift the child’s daily routines from working to schooling.